1998
DOI: 10.1007/bf02236897
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tumor proliferation of rectal cancer induced by preoperative 5-fluorouracil and irradiation

Abstract: The addition of 5-fluorouracil to preoperative irradiation resulted in a more complete inactivation of the proliferating population. Frequency of downstaging, however, was unaffected. Thus, the quiescent cell population appears to represent a substantial barrier to further downstaging. New treatment strategies should be aimed at controlled recruitment of quiescent tumor cells at the time of irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…PCNA immunostaining has proven to be a simple and useful method for the estimation of cell proliferation within tumors [24]. Our results agree with those of Willett et al [25, 26], indicating that proliferating cells are more responsive to radiation damage. The presence of a high PCNA index was statistically associated with a higher probability of a significant histologic tumor response to preoperative chemoradiotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…PCNA immunostaining has proven to be a simple and useful method for the estimation of cell proliferation within tumors [24]. Our results agree with those of Willett et al [25, 26], indicating that proliferating cells are more responsive to radiation damage. The presence of a high PCNA index was statistically associated with a higher probability of a significant histologic tumor response to preoperative chemoradiotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…9 Ki-67 proliferative activity is probably associated with the downstaging of highly proliferative tumors and the greater populations of quiescent cells in tumors resistant to downstaging. Willet et al 4 reported that tumor downstaging is influenced by growth fractions, such as PCNA (proliferative cell nuclear antigen) or Ki-67 staining. Moreover, rectal cancer with evidence of high growth fraction was found to be more likely to be downstaged.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, molecular genetic studies have been used to identify some of the genetic factors related to the wide spectrum of tumor radioresponsiveness. Willet et al 4 observed that tumor components with a low proliferative index do not respond well and that highly proliferative tumors generally show good response. Recently, the tumor suppressor genes, p53 and p21, which regulate the cell cycle and apoptosis, have been proposed to play major roles in tumor response to radiotherapy and chemotherapy.…”
mentioning
confidence: 98%
“…However, the benefit from preoperative radiation varies significantly in trials with a substantially wide pCR (9%-37%) [6][7][8][9][10] . Patients who achieve a pCR have better outcomes compared to patients who do not [11] .…”
Section: Introductionmentioning
confidence: 99%